Evaluation of high resolution melting technique for detection of JAK2-V617F mutation in formalin-fixed paraffin-embedded specimen from myeloproliferative neoplasm cases - Abdullahi, Mohammad Reza; Abdullah, Nor Zamzila; Ismail, Rosmawati; Muhammad, Siti Aeshah @ Naznin; A.Talib, Norlelawati (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Introduction: Myeloproliferative neoplasm (MPN) is a group of myeloid disorders which leads to erythrocytosis, thrombocytosis and leucocytosis. MPN with BCR-ABL positive is chronic myeloid leukaemia (CML) while BCR-ABL negative MPN includes polycythaemia Vera (PV), essential thrombocytemia (ET) and primary myelofibrosis (PMF). One of the major criteria for diagnosis of BCR-ABL negative MPN is the presence of JAK2-V617F mutation which is positive in 95% of PV and around 60% of ET and MF. Beside peripheral blood specimen, formalin-fixed paraffin-embedded (FFPE) marrow specimen can be used for detection of this mutation. Unfortunately, FFPE produces low quality DNA that put a challenge for successful amplification of DNA. We aimed to evaluate the utility of High Resolution Melting (HRM) analysis for detection of JAK2-V617F mutation in FFPE specimen from MPN cases. Materials and Methods: This study is a descriptive crosssectional study. Forty FFPE marrow specimens were retrieved from the years 2014-2016. Bio-Rad Precision Melt Analysis software was used for analysis of HRM data. Allele-specific PCR was done for validation of results. Positive samples were subjected to Sanger sequencing. Results: JAK2-V617F mutation was positive in 13 out of 40 MPN cases. Level of agreement between HRM and AS-PCR was 97.5%. Conclusion: HRM is a rapid and powerful diagnostic assay which is suitable for detection of JAK2-V617F mutation in FFPE marrow specimen.